Measuring the passion of entrepreneurship spirit on students in industrial revolution era 4.0 - LA Sylvia Chandradevi Widana; Gede Sri Darma (Journal of Business on Hospitality and Tourism, 2021)
The aim of this research is to observe the effect of self-efficacy, earning expectation and endorser credibility on the entrepreneurial interest and entrepreneurial readiness. This research was done in Undiknas Graduate School. The research design was quantitative research, which was a causality relationship between the variables. The technique of collecting data was done using questionnaire to 102 students. The technique of analyzing data was done using structural equation modeling (SEM) with AMOS version 22 program. The result of this research showed self-efficacy had a positive and significant effect of 0,429 on the entrepreneurial interest and 0,416 on the entrepreneurial readiness. Earning expectation had a positive and significant effect of 0,454 on the entrepreneurial interest and 0,198 on the entrepreneurial readiness. Social media had a positive and significant effect of 0,363 on the entrepreneurial interest and 0,440 on the entrepreneurial readiness. Advertisement effectiveness had a positive and significant effect on the entrepreneurial readiness of 0,595.